The Effect of Government Expenditure on Economic Growth in Indonesia - Lelly Cesarina Maulid; Icuk Rangga Bawono; Yudha Aryo Sudibyo (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to examine and analyze the effect of economic growth classified as personnel expenditure, material expenditure, capital expenditure, interest payments, subsidies and social expenditure in Indonesia. The data in this study are time series data from 2005 to 2019. The hypothesis test uses the multiple linear regression method with SPSS 26. The results of testing government expenditure variables during the period 2005 to 2019 shows that components of central government expenditure include personnel, material, capital, interest payments, subsidies and social expenditure have a significant effect simultaneously on economic growth. There is a significant positive effect on the relationship between the variable personnel expenditure and material expenditure on economic growth. There is a significant negative effect on the relationship between the variable capital expenditure on economic growth. The other three variables, which include debt interest payments, subsidies and social expenditure, do not have a significant effect on economic growth.